Sleep and nocturnal acid reflux in normal subjects and patients with reflux oesophagitis. Issue 11 (November 1991) - Freidin, N; Fisher, M J; Taylor, W; Boyd, D; Surratt, P; McCallum, R W; Mittal, R K
Abstract : Nocturnal gastro-oesophageal reflux may be important in the pathogenesis of reflux oesophagitis. This study aimed to determine whether: (1) gastro-oesophageal reflux occurs during sleep in patients with reflux oesophagitis and, if so, to explore the mechanism, and (2) the sleep pattern of patients with oesophagitis is different from that of control subjects. After a standard evening meal, simultaneous manometric, oesophageal pH, and polysomnographic recordings were obtained in 11 patients with endoscopic oesophagitis and 11 control subjects. Patients with gastrooesophageal reflux disease had significantly more total reflux episodes throughout the nocturnal monitoring period than control subjects (105 v 6). Ninety two of 105 episodes of gastro-oesophageal reflux in patients occurred during the awake state and 10 during sleep stage II. A number of reflux episodes occurred during brief periods of arousal from the various sleep stages. Of the 105 reflux events recorded in patients, 42 were induced by transient lower oesophageal sphincter relaxation, 20 by stress reflux, 22 by free reflux mechanisms, and in 21 the mechanism was unclear. The sleep pattern and the time spent in each sleep stage was not different between the two groups. It is concluded that the awake state is crucial for the occurrence of nocturnal reflux episodes in normal subjects as well as in patients with reflux oesophagitis and that the difference between the frequency of gastro-oesophageal reflux between normal subjects and patients cannot be explained by different sleep patterns.